High Concentrator Photovoltaics Fundamentals, Engineering and Power Plants - Pérez-Higueras, Pedro; Fernández, Eduardo F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The aim of this book is to provide a comprehensive overview of the fundamentals and engineering of high concentrator photovoltaic (HCPV) technology and to elucidate how this complex and emerging technology is applied in power plants. It is the first of its kind to focus exclusively on HCPV technology, and offers a valuable reference volume to readers. This book is the result of an international collaboration among experts, and each chapter is written by a specialist in the field. The conversion of solar energy to electricity plays an important role in power generation, and HCPV is signalled by many researchers and professionals as one of the most promising sources of solar power. Therefore this book provides an important resource for companies, research institutes and universities to assist with the understanding of fundamentals, different applications and potential of such technology.
Introduction -- Multi-Junction Concentrator Solar Cells: Analysis and Fundaments -- Characterization of Multi-Junction Concentrator Solar Cells -- High Concentration Optics for Photovoltaic Applications -- The High Concentrator Photovoltaic Module -- Modelling of High Concentrator Photovoltaic Systems for Utility-Scale Applications -- Shading in High Concentrator Photovoltaic Power Plants -- High Concentrator Photovoltaic Systems Configuration and Inverters -- Efficiencies and Energy Balance in High Concentrator Photovoltaic Devices -- Solar Resource for High Concentrator Photovoltaic Applications -- Standards for Testing High Concentrator Photovoltaic Modules -- Applications of ANNs in the field of the HCPV technology -- Building Integration of High Concentration Photovoltaic Systems -- Analysis of Present and Future Financial Viability of High Concentrating Photovoltaic Projects -- Economic Evaluation of HCPV systems -- High Concentrator Photovoltaic Power Plants: Energy balance and Case Studies.
Keywords: Renewable energy resources; Energy systems; Renewable and Green Energy; Energy Systems; Energy Systems